Magnetic reduced graphene oxide nanocomposite as an effective electromagnetic wave absorber and its absorbing mechanism. Issue 15 (15th November 2016) - Huang, Ying; Ding, Xiao; Li, Suping; Zhang, Na; Wang, Jianguo
Abstract: A magnetic reduced graphene oxide (MRGO) composite consisting of graphene oxide and Fe3 O4 particles in the range of 5–20 nm has been prepared by the one-pot hydrothermal process. RGO nanosheets provide flexible substrates for nanoparticle decoration, while Fe3 O4 nanoparticles can also effectively prevent nanosheets to restack each other. Compared with previously literature, the synthesized RGO-Fe3 O4 composite exhibits excellent electromagnetic wave absorption. The minimum reflection loss (RL ) value of −49.05 dB has been observed at 14.16 GHz with a thickness of 2.08 mm. The absorption bandwidth (RL <−10 dB) corresponding to the minimum RL is 4.60 GHz. The electromagnetic wave absorption properties of the RGO-Fe3 O4 composite have been interpreted through the quarter-wavelength matching model.